(18)F-FLT PET predicts response to (V600E)BRAF-targeted therapy in preclinical models of colorectal cancer - McKinley, Eliot T. (2013)
Selective inhibition of oncogenic targets and associated signaling pathways forms the basis of personalized cancer medicine. The clinical success of (V600E)BRAF inhibition in melanoma, coupled with the emergence of acquired resistance, underscores the importance of rigorously validating quantitative biomarkers of treatment response in this and similar settings. Since constitutive activation of BRAF leads to proliferation in tumors, we explored (18)F-FLT PET to non-invasively quantify changes in tumor proliferation that are associated with pharmacological inhibition of (V600E)BRAF downstream effectors and that precede changes in tumor volume. METHODS: Human colorectal cancer (CRC) cell lines expressing (V600E)BRAF were used to explore relationships between up-regulation of p27 and phosphorylation of BRAF downstream effectors upon small molecule (V600E)BRAF inhibitor exposure. Athymic nude mice bearing (V600E)BRAF-expressing human CRC cell line xenografts were treated with a small molecule (V600E)BRAF inhibitor (or vehicle) daily for ten days. Predictive (18)F-FLT PET was conducted prior to changes in tumor volume. Correlations were evaluated among PET imaging, inhibition of p-MEK and p-ERK by western blot, tumor proliferation by histology, and small molecule exposure by MALDI imaging mass spectrometry (IMS). RESULTS: Treatment of CRC cell lines with PLX4720 reduced proliferation associated with target inhibition and up regulation of p27. In vivo, PLX4720 treatment reduced (18)F-FLT uptake, but not (18)F-FDG uptake, in Lim2405 xenografts prior to quantifiable differences in xenograft volume. Reduced 18F-FLT PET reflected a modest, yet significant, reduction of Ki67 immunoreactivity, inhibition of p-MEK and p-ERK, and elevated tumor cell p27 protein levels. Both (18)F-FLT PET and (18)F-FDG PET accurately reflected a lack response in HT-29 xenografts, which MALDI IMS suggested may have stemmed from limited PLX4720 exposure. CONCLUSIONS: We utilized preclinical models of CRC to demonstrate (18)F-FLT PET as a sensitive predictor of response to (V600E)BRAF inhibitors. Since (18)F-FLT PET predicted reduced proliferation associated with attenuation of BRAF downstream effectors, yet (18)F-FDG PET did not, these data suggest that (18)F-FLT PET may represent an alternative to (18)F-FDG PET for quantifying clinical responses to BRAF inhibitors.